A magnesium transporter is involved in the cesium ion resistance of the high-concentration cesium ion-resistant bacterium Microbacterium sp. TS-1 - Ishida, Yoshiki; Koretsune, Takahiro; Ishiuchi, Eri; Teshima, Miyu; Ito, Masahiro (Frontiers in Microbiology, 2023)
Cesium ion (Cs+) resistance has been reported in bacteria but is poorly understood as reports on Cs+-resistant bacteria have been limited. We previously reported a novel Cs+/H+ antiporter CshA implicated in Cs+-resistance in Microbacterium sp. TS-1. The present study used the same screening method to isolate novel Cs+-sensitive mutants and their revertants from TS-1. A comparative mutation site analysis using whole-genome sequencing revealed that MTS1_03028 encodes the Mg2+ transporter MgtE and is a candidate Cs+ resistance-related gene. We performed a bioinformatic analysis of MTS1_03028 and complementation experiments on Cs+ resistance in the TS-1 MTS1_03028 mutants Mut5 and Mut7 as well as Escherichia coli expressing MTS1_03028 in the presence of Mg2+. We established the role of MgtE in Cs+ resistance through a functional analysis of TS-1. Enhancing Mg2+ transport by expression of MTS_03028 conferred increased Cs+ resistance. When this strain was exposed to Cs+ concentrations exceeding 200 mM, CshA consistently lowered the intracellular Cs+ concentration. To our knowledge, the present study is the first to clarify the mechanism of Cs+ resistance in certain bacteria. The study findings offer important insights into the mechanism of bacterial resistance to excess Cs+ in the environment, suggesting the potential for bioremediation in high Cs-contaminated areas.